NUMERICAL ANALYSIS FOR NUSSELT NUMBER AND HEAT TRANSFER AUGMENTATION ON SOLAR AIR HEATER ROUGHENED WITH SQUARE RIB ROUGHNESS ON THE ABSORBER PLATE - Amit Kumar; Apurba Layek (AGRIBUSINESS JOURNAL, 2019)
Heat transfer rate on solar air heater system is generally achieved by suitable modification of absorber plate surface with acceptable geometry of rib roughness. In this paper a numerical study is performed using CFD based computational analysis of heat transfer augmentation equipped with the square rib roughness created artificially on the absorber plate. The 2D analysis is performed using ANSYS 16.2 Code with RNG k-ε turbulence model to investigate the heat transfer and fluid flow characteristics. The augmentation of heat transfer on increase of Reynolds number enhance the Nusselt number which is referred as energy gain ratio with the use of rib roughness was examined and their relative evaluation has been plotted. The parameter which is considered for the range of analysis is taken as relative roughness pitch (P/e), relative roughness height (e/D) and the Reynolds numbers (Re) ranging from 3800-18000. The enhancement of heat transfers due to rib roughness on the absorber plate have been compared with those for smooth ducts for the same flow and thermal boundary condition to determine the energy gain ratio of solar air heater. The result obtained by the present investigation shows that the maximum value of energy gain ratio is found to be about 1.93 times the smooth duct for the studied range of parameters.